The Covid-19 conjuncture: rearticulating the school/home/work nexus. Issue 4 (2nd October 2022) - Kenway, Jane; Epstein, Debbie
ABSTRACT: The Covid-19 pandemic is intensifying existing problems of economic asymmetry, and other injustices, between and within countries and regions around the world. It is thus imperative that sociological studies of education document its socio-cultural implications in different locations and on different scales. It is equally imperative that such studies have a historical perspective that asks what pre-existing social problems have been intensified and how such intensification is happening. This paper responds to these imperatives through the deployment of conjunctural analysis and related crisis and articulation theory. We discuss the global Covid-19 conjuncture as it emerged in the first seven months of 2020 and show how it articulated with the preceding conjuncture. Subsequently, we focus on the issues associated with closing and reopening schools and show how they were intertwined with reconfigurations of the school/home/work nexus. We consider these reconfigurations in two very different locations, Australia and South Africa.